Analysis of Risk Factors for Hypertension in Productive Age Communities in the Working Area of the North Sangatta Health Center - Husna, Husna; Pakki, Irfansyah Baharuddin; Wisnuwardani, Ratih Wirapuspita (Symbiohealth, 2024)
Hypertension is one of the health problems whose prevalence continues to increase in society, especially among the productive age. This study aims to determine the risk factors for hypertension in the productive age community in the work area of the North Sangatta Health Center. The research method used in this study is obsevively analytical with a case control design. Data were obtained from demographic data questionnaires and observation sheets for blood pressure calculations with a sample of 138 people. The variables analyzed included demographic factors (age, gender, education, occupation, ethnicity), lifestyle (smoking), and medical factors (family history of hypertension and diabetes). The results of the analysis showed that there was a significant relationship between age (P = < 0.05), occupation (P = >0.008), diabetes mellitus (P<0.001), hereditary history of hypertension (P>0.009) and the incidence of hypertension, while sex (P = >0.85), education (P>0.069), ethnicity (P>0.067), and smoking habits (P>0.170) did not have a significant relationship with the incidence of hypertension in the productive age community. It is proven that age, occupation, diabetes mellitus, and a history of hypertension are risk factors for the increase in hypertension cases in the work area of the North Sangatta Health Center.